Improving Students' Vocabulary Mastery Through Structured Listening Exercises - Fauzah , Nurul; Husni, Rifqi Muzaki; Heykal Fikri; Iqmal Wahyudi (Lahjatuna: Jurnal Pendidikan Bahasa Arab, 2025)
This study explores the impact of structured listening practice on enhancing vocabulary acquisition among Arabic language students at Pondok Pesantren Dalwa. Despite the critical role of listening skills in language acquisition, they are often underemphasized in traditional curricula. This research utilizes a qualitative case study design, involving first-year students enrolled in an intensive Arabic language program at Dalwa. Data were gathered through in-depth interviews with students and teachers, along with classroom observations. The findings indicate that structured listening exercises significantly contribute to vocabulary development by providing students with exposure to authentic language contexts and opportunities for active engagement. The results suggest that listening activities, when designed to match students’ proficiency levels and encourage participation, can substantially enhance both comprehension and vocabulary retention. The study highlights the need for incorporating structured listening into Arabic language teaching programs, especially in Islamic boarding schools, and offers practical recommendations for educators in similar settings.